To Assess the Role of Immune Infiltrating Immune Cells of Patients With Chronic Heart Failure With Atrial Fibrillation and Nursing Care in These Patients: Role of Immune Infiltrating Immune Cells - ShuJun Liu,; QingYan Yang,; Liu, Jianxia; Qi Zhang,; Jing Zhang, (Cellular and Molecular Biology, 2023)
This research aimed to assess the role of immune infiltrating immune cells of patients with chronic heart failure with atrial fibrillation and nursing care in these patients. For this aim, 400 patients from 22 centres across our nations were recruited in the index cohort based on worsening signs/symptoms and poor management of HF. The validation cohort consisted of patients who had previously participated in the index cohort. The primary goal was to reduce all-cause mortality as well as unscheduled hospitalisations due to heart failure. Hospitalizations for heart failure (HF), total mortality, and death attributable to cardiovascular disease were secondary objectives. Results showed that interleukin-6 (IL-6) levels in patients ranged from 3.1 to 11.21 pg/mL on average, with 228 patients (or 57% of the total) having IL-6 levels that were higher than the 95th percentile of normal values (> 4.45 pg/mL). The average age of the group was 69.85±9.68 years, and there were 295 males in the group (73.75 percent). 17 Patients who had higher levels of IL-6 tended to be older, more frequently suffered from heart failure with preserved ejection fraction (HFpEF), and more frequently suffered from anaemia, diabetes, and atrial fibrillation. Patients who had higher levels of IL-6 also had a greater likelihood of suffering from these conditions. Patients who had higher levels of IL-6 also had a shorter distance travelled during the 6MWT and had a lower chance of completing the test. Both test completion [OR (95% CI) per doubling of IL-6: 0.81 (0.71 - 0.91), P< 0.001] and total distance covered [B (95% CI) per doubling of IL-6: 28.11 (32.58 to-21.98), P< 0.001] were negatively associated with increasing levels of IL-6, Patients who had high levels of IL-6 had higher median hepcidin levels than patients who had low levels of IL-6. This was discovered by comparing the two groups' hepcidin levels. There was a correlation between increased levels of IL-6 and increased levels of NT-proBNP and CRP, as well as a reduction in eGFR. In conclusion, independent predictors of IL-6 were younger age, high-flow partial ejection fraction (HFpEF), atrial fibrillation (AF), iron insufficiency, and higher levels of NT-proBNP, PCT, hepcidin, and TNF-/IL-1 related biomarkers. Last but not least, IL-6 levels in the plasma were able to predict death and/or hospitalisation due to HF on their own, although they did not contribute to differentiation in prior models.